The reality of the internal audit function in light of the digital transformation: an analytical reading of the outputs of the Dutch digital experience - heroual, mohamedamine; ziani, abdelhak (Journal of Research in Finance and Accounting, 2023)
This study aimed to shed light on the reality of the internal audit function in light of the outputs of digital transformation (digital transformation techniques), by addressing the analysis and study of a joint report between the Institute of Internal Auditors (IIA) and Ernst Young (EY) company for Auditing and Consulting, Which in turn relied on a questionnaire addressed to a sample of Dutch companies, where the number of distributed questionnaires was 73. The study concluded a number of results, most notably: that the Dutch companies under study are still relatively recent in using digital transformation techniques within internal audit activities, as there are many obstacles that prevent the adoption of these technologies, the most important of which are (cost, level of effort, lack of skills among internal audit staff).